2020
DOI: 10.1088/1757-899x/671/1/012143
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Electrical Efficiency of a Photovoltaic/Thermal Panel by Using SiC/Water Nanofluid as Coolant

Abstract: For photovoltaic panels, high temperature has a major effect, reducing electrical efficiency and decreasing the panel’s life span. In this work, an aluminum pocket collector was manufactured and fixed to the rear side of a photovoltaic panel to form a photovoltaic/thermal system (PV/T). A SiC/water nanofluid was used as coolant fluid with two volumetric concentrations (0.1 and 0.5%). The experiments were conducted outdoors at Babylon University (32.46 °N,44.42°E) in March. Different flow rates of SiC/Water nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Cooling the photovoltaic cells with nanofluids with different concentrations and base fluid such as ethylene glycol has shown a better enhancement than water as a base fluid (Esfe et al 2014). An efficiency enhancement of 33.27% when using an aluminum box of 3-mm thickness and SiC nanoparticles with water-based fluid at a concentration of 0.5% and a flow rate of 2 l/min as reported by Abbood et al (2020). A comparative study is made between Al 2 O 3 , CuO, and Al 2 O 3 -CuO mixture nanofluids (Shankar Amalraj et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cooling the photovoltaic cells with nanofluids with different concentrations and base fluid such as ethylene glycol has shown a better enhancement than water as a base fluid (Esfe et al 2014). An efficiency enhancement of 33.27% when using an aluminum box of 3-mm thickness and SiC nanoparticles with water-based fluid at a concentration of 0.5% and a flow rate of 2 l/min as reported by Abbood et al (2020). A comparative study is made between Al 2 O 3 , CuO, and Al 2 O 3 -CuO mixture nanofluids (Shankar Amalraj et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid nanofluid composed of alumina and carbon nanotubes (CNT) and water is utilized for active cooling using a spiral tube collector compared with non-cooling PV (Sathyamurthy et al, 2021), and they reported that the values of % was 17.2%, 16% and 14.8% for the three PV/T systems, correspondingly. Silicon carbide nanoparticles water-based nanofluid comparative study by (Abbood et al, 2020) used volume concentrations from 0.1% and 0.5% in contrast to water, which fill an aluminum rectangular of 3 mm height that circulated by a flow rate with different flow rates (0.5 -2) liter per minute. The electrical output of these two solar modules is compared with another one that was not cooled, and they found a maximum electrical improvement at a concentration of 0.5% and flow rate of 2 liter/minute.…”
Section: Introductionmentioning
confidence: 99%